2017
DOI: 10.1186/s41016-017-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of brain metastasis of lung squamous cell carcinoma: a retrospective analysis of 188 patients from single center

Abstract: Background: To explore risk factors and the efficacy of treatment strategies for brain metastasis (BM) in squamous cell carcinoma (SCC) of the lung. Methods: The clinical data of 188 pathologically confirmed as squamous cell carcinoma or adenosquamous carcinoma patients were studied retrospectively. Factors including age (<60 vs. ≥60), gender, stage at diagnosis, T status (T1-2 vs. T3-4), N status (N0-1 vs. N2-3), histology (squamous vs. adenosquamous), smoking history (non-smoker vs. current smoker) and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It was found that 40% of NSCLC patients had brain metastases. 14 Based on a study by He, et al (2021), 39% of lung squamous cell carcinoma patients had brain metastases. 15 Li, et al (2017) said that females and high CEA levels are factors associated with the incidence of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that 40% of NSCLC patients had brain metastases. 14 Based on a study by He, et al (2021), 39% of lung squamous cell carcinoma patients had brain metastases. 15 Li, et al (2017) said that females and high CEA levels are factors associated with the incidence of brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…14 Based on a study by He, et al (2021), 39% of lung squamous cell carcinoma patients had brain metastases. 15 Li, et al (2017) said that females and high CEA levels are factors associated with the incidence of brain metastases. 14 Both factors are consistent with the patient in this case report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations